THE HISTORY OF VISUAL ART AND ITS CONTEMPORARY RELEVANCE: EVOLUTION, INFLUENCE, AND PEDAGOGICAL IMPLICATIONS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article provides a comprehensive examination of the historical development of visual art and its sustained relevance in the context of 21st-century culture, education, and digital innovation. By tracing artistic evolution from prehistoric cave paintings to contemporary digital installations, the study emphasizes how visual art reflects sociocultural dynamics and contributes to human cognition, identity, and communication. Drawing from Scopus-indexed scholarly sources, historical records, and educational frameworks, the article critically evaluates the role of visual art in modern society and its integration into interdisciplinary and technological learning environments.